Magnetic and Microwave Absorbing of Mn(1-x)NdxFe2O4 Synthesized with Co-Precipitation Method - Adha, Mia; Yunasfi, Y.; Nurhasni, N. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Characterization of magnetic and microwave absorbing properties of Mn(1-x)NdxFe2O4 synthesized with co-precipitation method have been carried out. Mn(1-x)NdxFe2O4 (with x = 0.0; 0.4; and 0.8) powders was synthesized from mixture of NiCl2, NdCl3 and FeCl3 in mole ratio. Mixing of this powders were soluted with NH4OH 4M up to pH = 9.0. The formed precipitate were washed with demineralized water up to pH = 7.0 and then dryed at 120 oC for 5 h, sintered at 1200 for 3 h. Phase identification with X-ray diffractometer (XRD) have formed composite multiphases, which indicated by the appearance of MnFe2O4, NdFeO3 and Fe2O3 phase. The magnetic measurement using VSM (vibrating sample magnetometer) showed that the sample exhibited a ferromagnetic behavior, the Ms value is lower (in the range of 30 – 11 emu/g) while the Hc value is greater (in the range of 111 – 132 Oe) with increased concentration of Nd3+ ion (x values). Measurement by VNA (Vector Network Analyzer) showed the ability of absorption of microwaves increased with increasing content of Nd3+ ion, the composition of x = 0.0 at about 70% and addition of Nd3+ ion up to composition x = 0.8 at about 91%. Keywords: MnNd ferrite, co-precipitation methode, magnetic properties, microwave absorption